The effect and safety of preoperative biliary drainage in patients with hilar cholangiocarcinoma: an updated meta-analysis - Fei Teng; You-yin Tang; Jun-long Dai; Yongkun Li; Zhe-yu Chen (World Journal of Surgical Oncology, 2020)
Abstract Background The effect and safety of preoperative biliary drainage (PBD) in patients with perihilar cholangiocarcinoma are still controversial; the aim of our study is to evaluate all aspects of PBD. Methods All included studies featured PBD versus non-PBD (NPBD) groups were from 1996 to 2019 and were extracted from Cochrane Library, Embase, PubMed, and Science Citation Index Expanded. Results Sixteen studies met the inclusion criteria and were included in this analysis. PBD may lead to a significantly higher incidence of overall morbidities (OR 0.67, 95% CI 0.53, 0.85; P = 0.0009) and intraoperative transfusions (OR 0.72, 95% CI 0.55, 0.94; P = 0.02); moreover, bile leakage (OR 0.58, 95% CI 0.24, 1.41; P = 0.04), infection (OR 0.31, 95% CI 0.20, 0.47; P < 0.00001), and cholangitis (OR 0.18, 95% CI 0.007, 0.48; P = 0.0007) are also related to PBD. However, NPBD was associated with more frequent hepatic insufficiency (OR 3.09, 95% CI 1.15, 8.31; P = 0.03). In the subgroup meta-analysis, the differences in the outcomes of bile leakage and overall morbidity lost significance between the PBD and NPBD groups when the mean total serum bilirubin (TSB) concentration was above 15 mg/dl. Conclusion Meta-analysis demonstrated that compared to NPBD, PBD is associated with a greater risk of several kinds of infection and morbidities, but its ability to reduce postoperative hepatic insufficiency cannot be ignored. In patients with a high TSB concentration, PBD tends to be a better choice. However, these results need to be confirmed in a future prospective randomized trial with large samples to clarify the effects and find a specific TSB concentration for PBD.